Double induction strategy including high dose cytarabine in combination with all-trans retinoic acid: effects in patients with newly diagnosed acute promyelocytic leukemia - Lengfelder, Eva; Reichert, A.; Haferlach, Claudia; Haase, D.; Haferlach, T.; Löffler, H.; Staib, P.; Heyll, A.; Seifarth, Wolfgang; Saußele, Susanne; Fonatsch, C.; Gassmann, Winfried; et al. (Leukemia, 2000)
A prospective multicenter study was performed to investigate the clinical and molecular results of intensified double induction therapy including high-dose cytarabine (ara-C) in combination with ATRA in newly diagnosed acute promyelocytic leukemia (APL), followed by consolidation and 3 years maintenance therapy. Fifty-one patients, diagnosed and monitored from December 1994 to June 1999, were evaluated. The median age was 43 (16-60) years. The morphologic diagnosis was M3 in 40 (78%) and M3v in 11 (22%) patients. In 15 (30%) patients the initial white blood cell counts were ⩾5 × 109/l. The cytogenetic or molecular proof of the translocation t(15;17) was a mandatory prerequisite for eligibility. The diagnosis was confirmed by karyotyping in 46 and by RT-PCR of the PML/RARα transcript in 45 cases. The rate of complete hematological remission was 92% and the early death rate 8%. Monitoring of minimal residual disease by RT-PCR of PML/RARα (sensitivity 10−4) showed negativity in 29 of 32 (91%) evaluable cases after induction, in 23 of 25 (92%) after consolidation, and in 27 of 30 (90%) during maintenance, after a median time of 2, 4 and of 18 months after diagnosis, respectively. After a median follow-up of 27 months, the estimated actuarial 2 years overall and event-free survival were both 88% (79, 97), and the 2 years relapse-free survival 96% (90, 100). The high antileukemic efficacy of this treatment strategy is demonstrated by a rapid and extensive reduction of the malignant clone and by a low relapse rate. The results suggest that the intensity of the induction chemotherapy combined with ATRA is one of the factors which may have a critical influence on the outcome of APL. A randomized trial should assess the value of an induction therapy including ATRA and high-dose ara-C in comparison to standard-dose ara-C.
Gesehen am 13.04.2022